Comparative clinical outcomes of transcystic vs. transductal laparoscopic common bile duct exploration: a retrospective study - Xing-Guang Yang; Ming Hu; Wei-Feng Sun; Tian-Liang Zhang; Ji-Wu Yang; Hui-Qiong Zhao (BMC Gastroenterology)
Abstract Objective This study aims to compare the therapeutic outcomes of transcystic laparoscopic common bile duct exploration (TC-LCBDE) and transductive laparoscopic common bile duct exploration (TD-LCBDE) for the treatment of common bile duct stones accompanied by gallstones. Methods A cohort of 102 patients with common bile duct stones accompanied by gallstones, admitted between April 2016 and February 2025, were retrospectively analyzed. Based on the surgical approach, the patients were divided into Group A (TC-Group, n = 51) and Group B (TD-Group, n = 51). Group A underwent TC-LCBDE, while Group B underwent TD-LCBDE. Key parameters were statistically analyzed, including operative duration, intraoperative blood loss, postoperative length of stay, average hospitalization cost, postoperative drainage tube indwelling time, and the incidence of postoperative complications. Results Group A had a shorter postoperative length of stay compared to Group B (P < 0.05). The total hospitalization cost in Group A was also lower than that in Group B (P < 0.05). Additionally, the postoperative drainage tube indwelling time was shorter in Group A, with a statistically significant difference between the two groups (P < 0.05). Conclusion TC-LCBDE is an optimal surgical approach for treating common bile duct stones with concomitant gallstones, offering faster postoperative recovery, lower hospitalization costs, shorter hospital stays, and reduced drainage tube indwelling time. Clinical trial number Not applicable.